Management of Primary Biliary Cholangitis: Current Treatment and Future Perspectives - Barba Bernal, Romelia; Ferrigno, Bryan; Morales, Esli Medina; M. Castro, Cristina; Goyes, Daniela; Trivedi, Hirsh; Patwardhan, Vilas R.; Bonder, Alan (Turkish Journal of Gastroenterology, 2023)
Primary biliary cholangitis is an autoimmune cholestatic liver disease characterized by progressive destruction of bile ducts, which can ultimately progress to chronic liver disease and cirrhosis. Ursodeoxycholic acid and obeticholic acid are the only 2 Food and Drug Administration (FDA)-approved medications for primary biliary cholangitis. Unfortunately, up to 40% of patients with primary biliary cholangitis have an incomplete response to ursodeoxycholic acid, warranting an essential need for additional therapeutics. Peroxisome proliferator-activated receptor agonists have shown promising data supporting their use as disease-modifying therapies. Fibroblast growth factor-19 agonists, farnesoid X receptor agonists, and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 3 inhibitors are additional agents under investigation as potential disease-modifying therapy. However, evidence supporting the use of certain novel therapies over others is sparse. There is a need for additional clinical trials as well as research aimed at the underlying pathophysiology of primary biliary cholangitis to discover additional therapeutic targets. Cite this article as: Barba Bernal R, Ferrigno B, Medina Morales E, et al. Management of primary biliary cholangitis: Current treatment and future perspectives. Turk J Gastroenterol. 2023;34(2):89-100.